Recollections: Mark Tucker (1954-2000) - Jackson, Travis A. (Current Musicology, 2001)
Mark Tucker was one of those rare individuals who excelled in all the areas one might invoke in assessing a musical scholar’s importance. His two books and numerous essays on Duke Ellington and his public presentations on Thelonious Monk have all contributed to our recognition of him as a first-rate musicologist and jazz scholar, one whose work is beautifully written and brimming with insight. His research on Ellington’s early years has enhanced our understanding of how one of America’s most celebrated composers developed his craft. By situating Ellington in the complex worlds of Washington, D.C. and Harlem up to the 1930s, Mark helped open the door to a more nuanced investigation of jazz, going beyond hagiography or decontextualized musical analysis to render a complex portrait worthy of his subject. His unfinished monograph on Thelonious Monk promised to go in the same direction. A presentation for Columbia’s Center for Jazz Studies lecture series in 2000 showed Mark succeeding at disentangling Monk the myth from Monk the musician, and in the process bringing many who thought they understood Monk to a new level of awareness.